(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Lymphotoxin ?, ? and their receptor play an important role in the control of lymphoid organ development and support of immune responses against pathogens. Objective:To investigate expression of the lymphotoxin ?, ? and their receptor TL?Rs using immunohistochemistry technique in patients with chronic active hepatitis and hepatocellular carcinoma. Methods: Thirty five formalin fixed, paraffin embedded liver tissues, obtained from Liver and Digestive System Technical Hospital and private laboratories in Baghdad, were studied. In addition, thirteen apparently normal liver autopsies were collected from the Forensic Medicine Institute Archives after permission and used as control group. Liver tissue sections were cut at 4 µm and placed on positively-charged slides, used for the detection of lymphotoxin ?, ? and receptor TL?Rs by immunohistochemistry technique. Results:The expressions of lymphotoxin ?, ? and receptor TL?Rs were detected in most patients infected with HCV, 88%, 84%, 76% respectively in patient with chronic active hepatitis and 80%, 70%, 90% respectively in patients with hepatocellular carcinoma while low level of expression of these markers was observed in healthy control group. Conclusion: Lymphotoxin ?, ? and their receptor TL?Rs may play an important role in the development and progression of HCV associated liver pathology. Key words: lymphotoxin, TLR, carcinogenesis hepatocellular carcinoma.